Risk governance and financial performance: An empirical analysis - Olayinka Erin; Omololu Bamigboye; Jonah Arumona (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study examines the influence of risk governance on financial performance of 50 quoted firms in the Nigerian financial sector for the period of five years (2013-2017). Panel data was used to examine how the risk governance variables (Enterprise Risk Management_index, Chief Risk Officer_presence, Board Risk Committee_size, Board Risk Committee_activism, and Board Risk Committee_independence) affects financial performance (Return on Asset). The study reveals empirically that most of the risk governance variables (ERM_index, CRO_presence, BRC_activism, and BRC_independence) have a significant and positive impact on the performance of the firm with the exception of BRC_size which shows a negative association with the financial performance of the studied firms. The study empirically reveals that strong Chief Risk Officer (CRO) presence, effective board risk committee, and inclusion of independent directors in the risk committee will go far in serving as factors that would improve the performance of firms in today's financial environment. This study made a lot of core findings that contribute to the emerging literatures on risk governance and risk management research.
Keywords: M21; M40; M41; 650; board risk committee; chief risk officer; financial performance; Nigerian financial sector; return on assets; risk governance